PERAN KOMUNIKASI INTERPERSONAL DALAM MENINGKATKAN KUALITAS HUBUNGAN SOSIAL DI ERA DIGITAL - Asidiq, Muhamad Firas; M , Supriadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the role of interpersonal communication in improving the quality of social relationships. The research uses a qualitative approach with a library research method by examining various relevant literature such as books, scientific journals, and previous studies. The findings indicate that interpersonal communication plays a crucial role not only as a medium for exchanging information but also as a means of building emotional closeness, trust, and strong social bonds among individuals. Effective interpersonal communication is characterized by openness, empathy, support, positive attitudes, and equality, which contribute significantly to creating harmonious and sustainable relationships. In addition, emotional intelligence is an important factor that supports the success of interpersonal communication, especially in managing emotions and resolving conflicts constructively. In the digital era, the shift from face-to-face communication to online interaction presents challenges in maintaining the depth and quality of social relationships. Therefore, a balance between direct and mediated communication is necessary. In conclusion, strengthening interpersonal communication skills is essential to enhance social relationship quality and maintain healthy social interactions in modern society.